Transformation of DHN1 gene and DHN promoter constructs into sugarcane calli, regeneration of the calli, and acclimatization of the plantlets - Hayati Minarsih; Fauziatul Fitriyah; Annisa Aulya Aksa; Turhadi Turhadi; Deden Sukmadjaya; Sustiprajitno Sustiprajitno (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2023)
Dehydrin is known to have an important role in plant response and adaptation to abiotic stresses including drought and high salinity. Previous research reported the isolation of the full-length coding sequence (CDS) of DHN1 from sugarcane var. PSJT 941, and it shares a high homology with DHN genes from sorghum and other sugarcane varieties. In this study, the full-length CDS was cloned under the constitutive CaMV35S promoter and transformed into sugarcane calli mediated by Agrobacterium tumefaciens. The DHN promoter, Pr-1DHNSo, was also successfully isolated from the sugarcane var. PSJT 941 and cloned into the pBI121 expression vector. The promoter construct was subsequently transformed into sugarcane calli of var. Kidang Kencana. Transgenic sugarcane carrying DHN1 gene and DHN promoter constructs were regenerated according to the standard protocol of sugarcane tissue culture. Optimization of an acclimatization protocol using modified post-rooting media was also conducted and the resulting protocol reduced the total mortality rates of the transformed plantlets. The presence of the gene and promoter constructs was periodically tested by PCR using specific primers. The genotyping results showed that the constructs were present for more than a year after transformation.